Electrolux : refrigeration and segmentation - Baack, Daniel W.; Harris, Eric G.; Baack, Donald ([London] : SAGE, 2016)
Electrolux offers a variety of refrigerators and other household goods in many countries all around the world. This case examines Electrolux's marketing practices and product designs across different cultures.
Originally Published in: Baack, D. W., Harris, E. G., & Baack, D. (2012). Electrolux: Refrigeration and Segmentation. In International marketing (pp. 153-154). Los Angeles: SAGE Publications, Inc. ISBN: 9781452226354.
Description based on online resource; title from home page (viewed on April 26, 2016).
Keywords: elektronické knihy; electronic books; Electrolux Group; Market segmentation -- Case studies; Export marketing -- Case studies